Multi-Stakeholder Synergy in Education Transformation in Disadvantaged Regions - Nora Susilawati; Gusmira Wita; Hendra Haldi; Irhas Fansuri Mursal; Evelynd Evelynd (LPPM Universitas PGRI Sumatera Barat, 2026)
Disadvantaged regions continue to face challenges in educational development, particularly program fragmentation, limited facilities and infrastructure, geographical barriers, and weak inter-institutional coordination caused by sectoral ego. Drawing on the perspectives of collaborative governance and governance network theory, this study aims to analyze how multi-stakeholder synergy drives education transformation in a disadvantaged region. The research employed a qualitative approach with a case study design. Data were collected through participant observation, in-depth interviews, and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing. The findings reveal that multi-stakeholder synergy functions as a cross-sectoral coordination mechanism that integrates the local government, regional apparatus organizations, nagari governments, companies, customary institutions, schools, and the community into a programmed, integrated, and coordinated education transformation agenda. This mechanism operates through vision alignment, strengthened communication, trust-building, facilitative regional leadership, and a clear division of roles in mobilizing financial, material, social, and logistical resources. This synergy contributes to transformative shifts in community mindsets toward education, expanded access for school dropouts, strengthened non-formal education, improved school infrastructure, expanded internet access in blind-spot areas, and the development of road access to remote schools through cross-sectoral self-managed initiatives. The study concludes that the effectiveness of education transformation in disadvantaged regions increases when local governments act as coordinators of collaborative networks and optimize the functions of existing local institutions without establishing new ones. The novelty of this study lies in the formulation of a locally grounded multi-stakeholder synergy model for educational transformation in disadvantaged regions, which demonstrates that collective action capacity can be built not through institutional expansion, but through the integration of formal institutions, customary structures, community participation, and local values of togetherness within an existing governance network.